THE USE OF SOCIOMATHEMATICS-BASED DIGITAL MEDIA ON STUDENTS' CREATIVITY AT MI MUHAMMADIYAH PANCASILA - Dayu Rika Perdana (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lampung, 2025)
The problem in this study is the low creativity of grade IV students because educators have not used and implemented attractive digital teaching materials. This study aims to determine the use of sociomathematics-based digital media on the creativity of grade IV students of MI Muhammadiyah Pancasila. The research method used in this study used a quasi experiment method with a research design, namely a non-equivalent control group design. Determination of the research sample using probability sampling technique. Data analysis techniques using normality test and homogeneity test. Data collection techniques using tests, interviews, observation sheets and documentation. Hypothesis testing uses the N-Gain test and shows positive results so that it can be concluded that the use of sociomathematics-based digital media can increase the creativity of grade IV students of MI Muhammadiyah Pancasila.